Full Day School Learning Model on the Formation of Religious Attitudes and Social Attitudes of Students - Vera Erawati (Journal La Edusci, 2025)
This study examines the implementation of the full day school model at Madrasah Ibtidaiyah Ar-Razzaq Pekanbaru and its role in shaping students’ religious and social attitudes. Using a qualitative descriptive approach, data were collected through observations, in-depth interviews, and documentation to explore how daily routines, character-building programs, and learning activities contribute to holistic student development. The findings show that structured practices such as Dhuha prayer, tahfidz, muroja’ah, literacy programs, extracurricular activities, and classroom habitualization significantly strengthen students’ religious values, discipline, empathy, cooperation, and social awareness. The full day school environment provides continuous guidance, allowing students to internalize Islamic values and positive behavior throughout the school day. However, the study also identifies variations in students’ character development influenced by home environment, parental involvement, and individual readiness. These results highlight the importance of strong school–family collaboration and sustained teacher support to optimize character formation. Overall, the full day school model at MI Ar-Razzaq demonstrates meaningful potential in fostering well-rounded, religious, and socially responsible students.